The landscape of non-coding RNAs in the immunopathogenesis of Endometriosis - Abbaszadeh, Mohammad; Karimi, Mohammadreza; Rajaei, Samira (Frontiers in Immunology, 2023)
Endometriosis is a complex disorder that is characterized by the abnormal growth of endometrial-like tissue outside the uterus.It is associated with chronic inflammation, severe pelvic pain, infertility, and significantly reduced quality of life. Although the exact mechanism of endometriosis remains unknown, inflammation and altered immunity are considered key factors in the immunopathogenesis of the disorder. Disturbances of immune responses result in reduced clearance of regurgitated endometrial cells, which elicits oxidative stress and progression of inflammation. Proinflammatory mediators could affect immune cells' recruitment, fate, and function. Reciprocally, the activation of immune cells can promote inflammation.Aberrant expression of non-coding RNA (ncRNA) in patient and animal lesions could be suggestive of their role in endometriosis establishment. The engagement of these RNAs in regulating diverse biological processes, including inflammatory responses and activation of inflammasomes, altered immunity, cell proliferation, migration, invasion, and angiogenesis are widespread and far-reaching. Therefore, ncRNAs can be identified as a determining candidate regulating the inflammatory responses and immune system. This review aims in addition to predict the role of ncRNAs in the immunopathogenesis of endometriosis through regulating inflammation and altered immunity based on previous studies, it presents a comprehensive view of inflammation role in the pathogenesis of endometriosis.